Síntese, nanoencapsulamento e atividade biológica de compostos triazenos - Freitas, Augusto Gonzaga Oliveira de (2012)
Compounds featuring triazenidic units constitute a versatile class of molecules for the preparation of new inorganic complexes with broad applications that include cancer therapy such as leukemia treatment. Gold-triazenide complexes exhibit recognized versatility in bioinorganic chemistry and medicine, which prompted their development as a basis for anticancer compounds. However, strategies to reduce non-specific cytotoxic effects from the administration of chemotherapy directly into the blood plasma are necessary, as for many other systems. In this regard, the use of polymeric nanoparticles allows not only reduction of side-effects, but also to promote site-specific delivery and controlled release. In this work, the aspects mentioned above have been incorporated into a new polymeric nanoparticles system containing triazenide compounds, and its application to leukemia therapy was investigated. First, the pre-ligand 1-(4-amidophenyl)-3-(4-acetilphenyl)triazene (1) and the complex 1-(4-amidophenyl)-3-(4-acetilphenyl)triazenide-(triphenilphosphine)gold(I) (2) were synthesized and fully characterized by spectroscopic techniques and X-ray diffraction in crystal. Then the compounds were evaluated for their potential antibacterial and antileukemic activities. In vitro studies indicated good antibacterial and antileukemic potential to triazenide complex, while the free ligand showed no biological activity. Subsequently, the pre-ligand (1) and complex (2) were encapsulated in polymeric nanoparticles (15-200 nm) with spherical core-shell micelar morphology, formed by block copolymers. For such compounds, the most efficient encapsulation method is by pre-film, with which encapsulation capabilities of up to 10% mcompound / mpolymer can be achieved for systems featuring poly[methacrylate 2-(dialkylamino) ethyl] or polystyrene cores. Afterwards, nanoencapsulation, loading and release kinetics studies were carried out using PEO-b-PG2MA-b-PDPA and PS-b-PAA copolymers.